ANALYSIS OF JUMP SERVE PREFIX STEP MOTION ON LEG POWER IN VOLLEYBALL ATHLETES TUNAS SEMARANG - Adam Hakim Fajar (Universitas Negeri Semarang, 2024)
Motion analysis is a study in sports science to analyze a movement and the results will be evaluated whether there is something wrong with the movement. This study aims to analyze the motion of the jump serve prefix to the leg power of Tunas Semarang athletes. The research conducted was a survey approach. The approach was carried out using data collection through tests and measurements. The subjects used were Tunas Semarang club athletes totaling 10 athletes with certain criteria, measurement of leg power using the vertical jump test and jump serve test, data processing using kinovea software version 0.9.5. The results of the data analysis obtained that Tunas Semarang athletes only use 2 types of prefix steps, namely athletes who use 2 prefix steps and athletes who use 3 prefix steps. Of these types 3 prefix steps are more effectively used referring to the results of the tests carried out. Leg power in Tunas Semarang athletes has 3 athletes with the highest points. The conclusion of this study found that Semarang Tunas athletes used 2 and 3 steps when jump serving, the ideal step refers to the results of the 3-step test, the prefix is more ideal new findings and for Semarang Tunas athletes to improve the quality of leg power by practicing hard because the average Semarang Tunas athlete only has a sufficient category. Further research is expected to look for errors and limitations of athlete motion when jump serving.